An atomistic study on the thermomechanical properties of graphene and functionalized graphene sheets modified asphalt. (September 2021) - Nie, Fenghua; Jian, Wei; Lau, Denvid
Abstract: Functionalized graphene is potential to become the next generation of modifier for asphalt pavements which require long-term durability in service. However, the reinforcing mechanism of graphene-based sheet towards mechanical performance of asphalt and the effect from functional groups remains unclear. In this study, the thermomechanical properties of graphene and functionalized graphene modified asphalt nanocomposites are investigated using molecular dynamics simulations. The shear capacity of asphalt nanocomposites at different temperature levels is evaluated through pullout test, and the details of interactions between functionalized graphene and asphalt matrix are characterized. Results show that hydrogen bond plays an important role in the reinforcement of asphalt nanocomposites. Polar components of asphalt are easier to interact with functional groups on graphene sheet, while nonpolar components interact with modifier by π−π stacking and mechanical entanglement, respectively. Graphene sheet with hydroxyl functional groups presents more effective reinforcement due to stronger hydrogen bond interactions. The shear resistance of asphalt nanocomposites decreases with increasing temperature due to the increment of intermolecular distance and free volume size. The in-depth understanding of reinforcing mechanism helps to provide information on more favorable functional groups, which is beneficial for manipulation and design of durable asphalt pavement materials using nano-engineering. Graphical abstract: Image 1